1967
DOI: 10.1037/h0024175
|View full text |Cite
|
Sign up to set email alerts
|

Socially facilitated reduction of the fear response in rats raised in groups or in isolation.

Abstract: Rats were tested in an approach-avoidance situation using food and shock. Experiment 1 involved 72 Ss in a 2 X 2 factorial design comparing the effects of group or individual testing following group or individual shock at the goal. Experiment 2 involved 48 Ss in a 2 X 2 factorial design comparing effects of rearing Ss in groups or in isolation on 2 of the conditions from Experiment 1. Ss tested in groups approached significantly more than those tested individually, whereas group vs. individual shock made no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
1

Year Published

1972
1972
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 3 publications
3
21
1
Order By: Relevance
“…It might be that the way laboratory rats are reared normally serves as a learning process which associates other members of the species with safety and satisfaction of primary needs. Angermeir et al (1965) and Morrison and Hill (1967), for example, have reported that for animals reared in isolation, the presence of other animals had little or no effect upon fear-reduction. On the other hand , for animals reared socially, the presence of other animals resulted in a reduction of fear-conditioned behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be that the way laboratory rats are reared normally serves as a learning process which associates other members of the species with safety and satisfaction of primary needs. Angermeir et al (1965) and Morrison and Hill (1967), for example, have reported that for animals reared in isolation, the presence of other animals had little or no effect upon fear-reduction. On the other hand , for animals reared socially, the presence of other animals resulted in a reduction of fear-conditioned behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…When the response prevention was done in the presence of two nonconditioned rats, the result was an increase in the efficacy of the response prevention technique in facilitating extinction. An important variable in the socially facilitated reduction of a fear response seems to be the Ss' social history; animals reared in isolation seem to be insensitive to this social phenomenon (Angermeier, Philhour, & Higgins, 1965;Morrison & Hill, 1967).…”
mentioning
confidence: 99%
“…It has also been observed that shock-induced fear does not necessarily lead to greater affiliative behavior in the laboratory rat, despite evidence that fewer signs of fear are present when animals are together than when alone (Latane, Friedman, & Thomas, 1972). In addition, a relationship has been demonstrated (Williams & Eichelman, 1971) between differential physiological responses, e.g., blood pressure change, in response to shock and the social setting in which the shock is administered.The possibility that stress is reduced by manipulating social variables is suggested by the work of Morrison and Hill (1967), who found socially facilitated fear reduction in an approach-avoidance situation. In order to examine the wider implications of the relationship between social conditions and stress, the current experiments sought to determine whether established dominant-submissive relationships in male rat pairs, as measured by mutual grooming, would .be affected by auditory stress under differential social settings.…”
mentioning
confidence: 99%
“…The possibility that stress is reduced by manipulating social variables is suggested by the work of Morrison and Hill (1967), who found socially facilitated fear reduction in an approach-avoidance situation. In order to examine the wider implications of the relationship between social conditions and stress, the current experiments sought to determine whether established dominant-submissive relationships in male rat pairs, as measured by mutual grooming, would .be affected by auditory stress under differential social settings.…”
mentioning
confidence: 99%
“…RESULTS Affiliation in the No-Shock Condition When alone in the shuttlebox, rats spent 60.4% of their time in the Rats, like many other animals, show fewer signs of fear when they are together than when they are alone. They defecate less, and they are less likely to freeze when in the presence of other rats (Davitz & Mason, 1955;Latane , 1969;Latane & Glass, 1968;Morrison & Hill, 1967). It is possible that one reason why rats affiliate is that, by doing so, they can reduce fear.…”
mentioning
confidence: 99%